2003
DOI: 10.1007/s00402-003-0517-9
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral luxatio erecta humeri

Abstract: Based on this case and the pertinent literature, the pathophysiology, diagnosis, and treatment of this rare injury are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…[7] The classical view, which is also characteristic, is the hyper-adduction of the affected arm, flexion of the elbow, and the hand positioned over or behind the head. [5,7,8] The unaffected hand supports the arm in order to stabilize the affected arm and alleviate the pain. On physical examination, the glenoid cavity is empty and the head of the dislocated humerus can be palpated in the axilla or over the chest wall.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[7] The classical view, which is also characteristic, is the hyper-adduction of the affected arm, flexion of the elbow, and the hand positioned over or behind the head. [5,7,8] The unaffected hand supports the arm in order to stabilize the affected arm and alleviate the pain. On physical examination, the glenoid cavity is empty and the head of the dislocated humerus can be palpated in the axilla or over the chest wall.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the pulling effect of the pectoralis major, the arm stays in the erected position. [7,10] There may be severe soft-tissue injury due to the avulsion of the supraspinatus, infraspinatus and teres minor muscles. There are some complications of LE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rotator cuff was reported intact [11]. There are also reports that make reference to the MRI findings without actual depiction; Mohseni reported inferior and superior labral tearing and fraying in a patient with LEH, and Karaoglu et al reported a patient with bilateral LEH and bilateral complete tears of the supraspinatus tendons [12,13].…”
Section: Resultsmentioning
confidence: 97%